2020
DOI: 10.1007/s41669-020-00234-7
|View full text |Cite
|
Sign up to set email alerts
|

Can Private Provision of Primary Care Contribute to the Spread of Antibiotic Resistance? A Study of Antibiotic Prescription in Sweden

Abstract: Background Growing rates of antibiotic resistance, caused by increasing antibiotic use, pose a threat by making antibiotics less effective in treating infections. Objective We aimed to study whether physicians working at privately and publicly owned health centres differed in the likelihood of prescribing antibiotics and choosing broad-spectrum over narrow-spectrum antibiotics. Methods To estimate the effect of ownership on the probability of a prescribed drug being an antibiotic, we analysed all 4.5 million p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…Due to a lack of case-mix the authors could not rule out that the differences could be explained by differences in patient characteristics. However, the same pattern was found by Granlund and Zykova [ 59 ] in a register study from one region. The results showed that physicians employed at private PHC centres were 6% more likely to prescribe antibiotics and 9% more likely to prescribe broad-spectrum antibiotics compared to physicians employed at public PHC centres.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Due to a lack of case-mix the authors could not rule out that the differences could be explained by differences in patient characteristics. However, the same pattern was found by Granlund and Zykova [ 59 ] in a register study from one region. The results showed that physicians employed at private PHC centres were 6% more likely to prescribe antibiotics and 9% more likely to prescribe broad-spectrum antibiotics compared to physicians employed at public PHC centres.…”
Section: Resultssupporting
confidence: 86%
“…A few studies have investigated differences between private and public PHC centres, of which three studies investigated prescription patterns and/or perceived quality. The prescription of antibiotics was investigated by Maun et al [ 58 ] and Granlund and Zykova [ 59 ]. In the study by Maun et al [ 58 ], the authors found a higher prescription rate of antibiotics for private PHC centres (6.0 vs. 5.1 prescriptions per 100 individuals in a quarter) but a lower prescription rate of benzodiazepines.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, there remains a powerful need to 'connect the dots' by providing a realist [39], applied and evidence-based conceptual model that maps the social ecology and potential areas for intervention to improve appropriate antibiotic prescribing. A recent study conducted in Sweden found that doctors in private practice were 6% more likely to prescribe antibiotics as compared to doctors in public practice [40], with a similar trend observed from another cross-sectional study conducted in Malaysia [41]. Instead of dissecting and addressing the issue of inappropriate antibiotic prescribing by different primary care funding structures, the current study offers a comprehensive exploration across private and public sectors.…”
Section: Discussionsupporting
confidence: 74%
“…41 This may in part explain the high antibiotic use in Finland as private providers may be more willing to prescribe antibiotics to secure patient satisfaction. 42 , 43 …”
Section: Discussionmentioning
confidence: 99%
“…41 This may in part explain the high antibiotic use in Finland as private providers may be more willing to prescribe antibiotics to secure patient satisfaction. 42,43 It has previously been found that antibiotic prescription rates and classes of antibiotics vary between different settings, which might be attributed to different guidelines and habits of prescriptions. 44 The high use of penicillins with extended spectrum in Finland is related to guidelines recommending amoxicillin (a penicillin with extended spectrum) as the first-line therapy for the treatment of otitis media.…”
Section: Discussionmentioning
confidence: 99%